'I worry about my family getting it': are we ignoring patient's agenda at the end of life?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Baker, Nicola; Armour, Kathy; Meystre, Chantal; Clifford, Collette
Abstract : There is increasing interest globally in the concept of 'health promoting palliative care' which aims to incorporate public health messages into palliative care services. However, there has been little emphasis on the prevention of ill health in palliative care. The role of palliative care in providing family-focused support, throughout a life limiting illness and into bereavement, means that opportunities to promote health in relatives and carers may be greater than in many other settings. Being a carer and subsequent bereavement can negatively impact on physical and emotional health. Furthermore, relatives of cancer patients are at increased risk of cancer themselves through shared genetic, environmental and lifestyle factors. While studies have evaluated family caregivers' requirements in terms of psychological support and information, none have focused on addressing their physical and emotional health needs. Few studies have looked at information needs from the wider family perspective. We performed a literature review, pilot questionnaire study involving patients, carers and hospice staff (for which MREC permission was obtained) and family focus groups, to explore the potential of a palliative care, family-focused health promotion programme. The literature describes leaving a 'healthy legacy' as an important part of fostering hope in cancer and palliative care patients. Patients in our pilot study and focus groups described concerns for their family's health and valued opportunities to discuss these. It was found that relatives and carers would welcome more information regarding their health and emotional wellbeing, but concerns were raised particularly by hospice staff. We will use the results of our investigations to inform further qualitative studies and to define the potential benefits of, and barriers to a health promotion programme aimed at families of palliative care patients.